2011
DOI: 10.1590/s0100-29452011005000003
|View full text |Cite
|
Sign up to set email alerts
|

Papaya pulp gelling: is it premature ripening or problems of water accumulation in the apoplast?

Abstract: -Gelled aspect in papaya fruit is typically confused with premature ripening. This research reports the characterization of this physiological disorder in the pulp of papaya fruit by measuring electrolyte leakage, Pi content, lipid peroxidation, pulp firmness, mineral contents (Ca, Mg and K -in pulp and seed tissues), and histological analysis of pulp tissue. The results showed that the gelled aspect of the papaya fruit pulp is not associated with tissue premature ripening. Data indicate a reduction of the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 27 publications
(22 reference statements)
3
10
0
Order By: Relevance
“…However, fruits with flesh translucency could have multiple causes that lead to same symptoms. Oliveira et al (2010) showed that Ca ++ levels were neither different (Pb 0.05) in seeds nor the pulp of the flesh translucency of the papaya when compared with healthy fruit. Similarly, pulp firmness was also not found to differ from that of healthy material (Oliveira et al, 2010) implying that papaya pulp flesh translucency is unrelated to the Ca ++ deficiency, but more specifically to the proton pumps (Azevedo et al, 2007).…”
Section: Decmentioning
confidence: 88%
See 3 more Smart Citations
“…However, fruits with flesh translucency could have multiple causes that lead to same symptoms. Oliveira et al (2010) showed that Ca ++ levels were neither different (Pb 0.05) in seeds nor the pulp of the flesh translucency of the papaya when compared with healthy fruit. Similarly, pulp firmness was also not found to differ from that of healthy material (Oliveira et al, 2010) implying that papaya pulp flesh translucency is unrelated to the Ca ++ deficiency, but more specifically to the proton pumps (Azevedo et al, 2007).…”
Section: Decmentioning
confidence: 88%
“…Physiological disorders of the most varied causes are common in many fruit species (Chatenet et al, 2000;Paull & Reyes, 1996;Roper, 1999), and the papaya is not an exception (Kaiser, Allan, White, & Dehrmann, 1996;Oliveira et al, 2010;Reyes, Eloisa, & Paull, 1994;Schripsema, Vianna, Rodrigues, Oliveira, & Franco, 2010). These disturbances are almost always related to environmental factors Oliveira, Pereira, Martelleto, & Ide, 2005;Oliveira et al, 2004;Oliveira et al, 2002) which, in certain cases, are difficult for growers to prevent.…”
Section: Physiological Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission electron microscopy analysis previously performed by Campos et al (2004) and Oliveira et al (2010) revealed that the pulp tissues in gelled papayas exhibited cells with intense plasmolysis and unbroken cell walls. The irregular contours of gelled tissue cells may be the result of excessive water loss from these cells to the apoplastic environment, which could account for the soaked appearance of the gelled mesocarp as suggested by Oliveira et al (2010).…”
Section: Introductionmentioning
confidence: 81%